PENGUNGKAPAN TATA KELOLA PERUSAHAAN DAN AKURASI HARGA SAHAM Bukti Empiris dari Usaha Kecil dan Menengah di Bursa Efek Indonesia Tahun 2018-2020 - Sri Felia Kurni; Muchamad Syafruddin (Diponegoro Journal of Accounting, 2022)
This research was conducted based on the approach of signalling theory. Signalling theory is to explain the relation between corporate governace disclosure with share price accuracy. The objective of this research is to investigate the impact of corporate governance disclosure on share price accuracy of small medium enterprise (SME) that listed on Indonesia Stock Exchange (IDX). Furthermore, this paper extends the literature on the relationship between accounting disclosure and share price accuracy to include corporate governance disclosure in emerging market economies such as Indonesia. It also shows the importance of both voluntary and mandatory corporate governance disclosure.This reserarch used secondary data from annual report of small medium enterprise (SME) that listed on Indonesia Stock Exchange (IDX) and share price accuracy records were created from each company’s weekly share price returns between 2018-2020, utilizing generalized least squares regression analysis. Multiple regression analysis with fixed effects was then implemented to test the study hypotheses. So, the results showed that the indipendent variabel consisting of voluntary and mandatory corporate governance disclosure has positive impact on share price accuracy in the Indonesia small business enterprise (SME) environment. But it does not have significant impact to share price accuracy.